Pemberdayaan Perempuan Pengrajin Tenun Melalui Pelatihan Desain Motif Untuk Mendukung Pengembangan Ekonomi Kreatif Di Desa Lanto - Alias, Alias; Hermina, Sitti; Sarman, Sarman (Syntax Literate, 2025)
This community service activity was carried out with the aim of enhancing the capacity of women weavers to support the development of the creative economy in Lanto Village, Mawasangka Tengah District, Central Buton Regency through motif design training. The background of this activity is based on the limited innovation in traditional weaving motifs, which tend to be repetitive and insufficiently represent the rich visual elements of the local environment. The method used was participatory, involving several stages: coordination and field survey, socialization and identification of natural potentials, motif design training, implementation of the designs into woven fabrics, and evaluation. The activity engaged 11 artisans from the Dasawisma Ar-Rahman group, with training conducted over five days, three hours per day. The results showed a significant improvement in design understanding and skills, and the successful creation of six new motifs, three of which were ready for application in woven products. The activity also fostered increased awareness and enthusiasm among the artisans to continue innovating. In conclusion, this training effectively empowered women weavers by strengthening creativity rooted in local wisdom, with strong potential to support cultural preservation and the development of the community-based creative economy.